Theorising the police support volunteer experience in an English constabulary: A role identity perspective - Pepper, Melissa (Policing and society, 2022)
Police Support Volunteers (PSVs) – citizens who give their time freely to perform tasks that complement the duties of police officers and staff – are a relatively new addition to a long and established history of volunteers in policing. However, despite featuring in every police service in England and Wales, little is known about the individuals who volunteer or their experiences while doing so. This article draws on interviews with 20 PSVs and five volunteer managers in a large urban police service in England. Findings point to the importance of volunteers being recognised and valued for their contribution, the ways in which this is communicated by paid members of the workforce, and the meaning that PSVs attach to feeling recognised and valued in terms of their satisfaction and intention to continue to give their time. The article frames the significance of PSV experiences through role identity theory – the aspects of an individual’s self-image that they derive from the social categories to which they perceive themselves belonging – which has been shown to be influential on the development of organisational commitment, volunteer satisfaction, and the subsequent sustained volunteering behaviour that this can bring about. The article concludes by highlighting the importance of embedding volunteer recognition throughout the police organisation, rather than relying on the tenacity of individual officers and staff members. It also acknowledges the opportunities that a role identity perspective brings to a currently under-theorised field, helping to make sense of PSVs’ experiences as a volunteer in policing.